Topical Issues of Value-Focused Engineering Education - N. D. Tskhadaya; D. N. Bezgodov (Высшее образование в России)
The article justifies the effectiveness of value-focused education as a strategic approach in education, integrating on a value basis the advantages of subject, personality and practice-oriented education. The axiological triad of university values: veritism, personalism, patriotism is considered as the corresponding value basis. The key structural contradiction of engineering education – between the requirements of the innovative economy to the content of modern engineering education and the environmental imperative – is identified and analyzed. The authors make the case for justifying the value profile of university organizational culture, and propose to refer to it as “axiologics of the university”. They also examine an essential distinction between “value” and “purpose” phenomena as a basis for an operational definition of “value.” Value ambivalence of the phenomenon of engineering is considered. The authors propose to interpret the Heidegger solution of the “question of technology” with regard to a dual challenge facing engineering education: training of a professional – on the one hand, and development of a personality – on the other hand. The authors consider university as a source and model of innovative economy, explore the phenomenon of the “innovation chain”.